(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present globalization, liberalization, and privatization have in total renewed whole Indian economy by empowering limit less business processes thereby providing more open doors for investors to choose the best investment. The high pace rise of Indian economy has renewed its business processes providing opportunities giving another dimensions for investors to investigate more chances and adding greater market share. The significant lines of enquiry in the corporate finance literature are the effect of corporate administration on firm value and execution. In the scholarly literature there is an alternate strand which clarifies this wonder. Under the organization theory, Shareholders may invest in the executive’s control of the firm since they discard a non-irrelevant share of the extra benefits and have a critical equity stake in the organization. Besides, they hold voting rights to impact administrators and may practice some degree of control or investment in the exercises of the firm. The attention on shareholder value has increased and given much significance in the years to come. In this research paper, we studied about the impact of shareholding pattern on firm’s value in detail.